Leadership Strategy Of School Principal In Improving Teacher Professionalism At Al-Yasiriyah Educational Foundation - Tanjung, Rizka Yulia; Harahap, Muhammad Yunan (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
This research aims to analyze the leadership strategies of school principals in improving teacher professionalism at Al-Yasiriya Brothers Educational Foundation. Using a descriptive qualitative research method with pedagogical and sociological approaches, this study involves school principals, teachers, and students as primary data sources. Data collection is conducted through direct observation, in-depth interviews, and documentary studies. Data analysis employs Miles and Huberman techniques, which include three stages: data reduction, data presentation, and conclusion drawing, with triangulation as a data validation method. The results reveal that school principals implement several key strategies to improve teacher professionalism. First, teacher competency development is carried out through ongoing professional training programs and workshops. Second, the creation of a collaborative working environment that fosters innovative learning. Third, the implementation of regular academic supervision to enhance teaching quality. Fourth, the application of performance-based reward systems to boost teacher motivation. The school principals also demonstrate transformational leadership by leading through discipline, integrity, and commitment to the foundation's vision. Despite facing challenges such as limited budgets and resistance to change, school principals have overcome these obstacles through effective communicative and collaborative approaches. This research concludes that the strategic leadership of school principals plays a fundamental role in improving teacher professionalism. Based on these findings, it is recommended to strengthen the synergy between school principals, teachers, and the foundation to create a quality and sustainable educational ecosystem